3C–, 4H–, and 6H–SiC crystal habitus and interfacial behaviours in high temperature Si-based solvents. Issue 20 (12th May 2020) - Narumi, Taka; Chaussende, Didier; Yoshikawa, Takeshi
Abstract : We investigated the stable habit planes of 3C–, 4H– and 6H–SiC in Si and Si–Cr-based solvents using Ostwald ripening of SiC particles, and found that particle-growth behaviour varied significantly with both SiC polytypes and solvent compositions. Abstract : Solution growth of SiC is a promising process for producing high-quality SiC crystals; however, control over the morphology of the growth interface under rapid growth conditions is a critical issue. To evaluate crystal habit and interfacial growth of SiC in the high temperature solution, we conducted Ostwald ripening of 3C–, 4H– and 6H–SiC fine particles in various solvents. First, the crystal habits of 3C–, 4H– and 6H–SiC particles were evaluated. We revealed that 4H–SiC exhibited 101̄2 in addition to 0001 and 101̄0 as habit planes. Next, the rates of particle-growth of SiC in Si, Si–40 mol%Cr and Si–40 mol%Cr–4 mol%Al solvents were evaluated. The particle size of 4H–SiC in Si–40 mol%Cr solvent was greater than that in Si solvent. Furthermore, particle growth was suppressed on adding Al to Si–40 mol%Cr solvent. The particle-growth behaviour suggested that Al addition decreased the interfacial energy between 4H–SiC and the Si–40 mol%Cr solvent.